Between and within race changes in race parameters in swimmers with intellectual disability - Einarsson, I. P.; Jóhannsson, E.; Daly, D. (1st International Scientific Conference of Aquatic Space Activities, 2008)
The purpose of this study was to examine the variability of diverse aspects of freestyle race performance in swimmers with intellectual disability (ID). Sixteen competitors (8 ID and 8 without ID) swam three 200-m freestyle races in competition over a 4 month period. Both groups had similar training background and competitive experience. ID swimmers showed a greater between race variability than the control group in end result (9.9% vs. 6.3% for WID) and mid-pool swimming speed. They also showed a greater variation in the relationship between change in Stroke Rate and change in swimming speed. ID swimmers swam slower and had not only a shorter Stroke Length but also lower Stroke Rate.